Momelotinib – a promising advancement in the management of myelofibrosis in adults with anemia - Furqan, Muhammad; Oduoye, Malik O. (Frontiers in Oncology, 2024)
Myelofibrosis (MF) is a rare BCR-ABL negative myeloproliferative neoplasm characterized by clonal proliferation of stem cells, with mutations in JAK2, CALR, or MPL genes. MF presents in primary and secondary forms, with common symptoms including splenomegaly, anemia, and thrombocytopenia. Diagnostic criteria involve bone marrow examination and mutation studies. Current treatments are limited, with allogeneic stem cell transplant as the only curative option. Recent FDA approval of Momelotinib (MMB) offers new promise for MF patients with anemia. MMB, a JAK1/2 and ACVR1 inhibitor, effectively reduces spleen size, improves hemoglobin levels, and decreases transfusion dependency. The MOMENTUM trial compared MMB to danazol in JAK inhibitor-treated MF patients with anemia, showing MMB's superior symptom relief and transfusion independence rates. Additionally, the SIMPLIFY-1 and SIMPLIFY-2 trials evaluated MMB in JAK inhibitor-naïve and experienced patients, respectively, confirming MMB's non-inferiority to ruxolitinib in spleen volume reduction and highlighting its benefits in transfusion requirements. MMB's unique dual inhibition mechanism addresses anemia by suppressing hepcidin production, thus enhancing erythropoiesis. These trials collectively suggest MMB as an effective treatment for MF, improving quality of life and offering a survival advantage for patients with anemia. Despite challenges, such as trial design limitations and adverse events, MMB represents a significant advancement in MF management, providing a new therapeutic option for a previously underserved patient population.